Behavior towards HIV among the Spouse of Male Migrants in Mid-western Nepal- A cross-sectional study - Mishra, D.; Basnet, G.; Yadav, U.N. (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background : Foreign labor migration has over the years, become major features of Nepal’s economy and society. In seek of opportunities; many of people of reproductive age group migrate to destination countries where they are exposed to risky behaviors. This study aimed to study HIV related knowledge and vulnerability of these women.Methods : The cross-sectional study was carried out among 150 spouses of migrant workers in Dhanauri VDC of Dang District. Semi-structured questionnaire was designed to collect the information from the respondents to meet objectives of the study. Data was analyzed by using SPSS(15.0). Ethical permission was obtained by Institutional Ethics Committee.Results: Almost all respondents had heard of HIV and AIDS and 55% had poor comprehensive knowledge on HIV prevention; 32% perceived HIV could transmit through mosquito bite; sharing meal of infection person (59.3%). The women ever discussed about sex with their husbands were 25.3%, among them 77.1 percent of spouse of male migrants doesn’t use condom during sexual intercourse during husband’s last visit at home. Major reason was they didn’t think it is necessary (88.1 percent) to use.Conclusion: The study revealed, despite great attention to HIV/AIDS program by Government and other agencies the knowledge on HIV prevention is below 50%. Comprehensive education program is needed to increase the level of correct knowledge on HIV prevention among wives of migrant workers. Targeted intervention among wives of migrant workers is important to make them able to negotiate for safe sexual practices with their husbands for HIV prevention and disclose their status for accessing services.Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.7-13